Evaluation of Speckle Variance, Higher Moments and Their Dependence on Incidence Angle. - Hallaråker, Jon Anders Vethe (UiT The Arctic University of Norway, 2018)
This thesis investigates speckle properties from Sentinel-1 GRDM data to explore its dependency of incidence angle. The data is processed using the SNAP-tool such that a uniform region can be selected and estimation of speckle variance, skewness and kurtosis can be carried out. These speckle properties are calculated over ocean and sea ice for comparison and modeled to fit a regression line. Hypothesis testing is carried out to determine the statistical significance. Due to the GRDM product having different number of multi-looks depending on the swath, a normalization is done to fit the regression line. It is shown that there is a slight decrease in variance over incidence angle with statistical significance for both ocean and sea ice. The response is however low. It is further shown that the trend in texture measurements such as skewness and kurtosis have a lower statistical significance and may be deemed to have little to no variation over incidence angle.